Sangiang Anyer Island Tourism Communication Strategy as a Nature Tourism Park - Pitasari, Dwi Nurina; Annisarizki, Annisarizki; Bella, Bella (Universitas Islam Negeri Raden Intan Lampung, 2022)
Sangiang Island has good potential as a tourist destination that can generate income for regional development but it is unfortunate that there is no tourism communication strategy, potential identification and good management on this island. The aim of the research is to identify the potential and challenges of developing natural tourism that belongs to Sangiang Island as a Natural Tourism Park (TWA) so as to be able to formulate a marketing communication strategy for Sangiang Island. The method used is descriptive qualitative with data collection techniques through observation, literature studies and interviews. This study uses a SWOT analysis. The results showed that the identification of Sangiang Island's tourism potential was natural tourism, marine tourism, cultural tourism and educational tourism.Keywords: Tourism Communication, Sangiang Island, SWOT analysis